UNDERSTANDING MOTIVATION IN SECOND LANGUAGE ACQUISITION: A STORY OF AN INDONESIAN EFL LEARNER - Sadri, Idris (VISION, 2024)
Second language acquisition is the process by which someone learns a second language (L2) in addition to their native language (L1). The acquisition of an L2 is a complex and multi-dimensional process, influenced by various factors such as age, motivation, exposure to the language, social and cultural factors, and individual differences in cognitive and learning abilities. This article will highlight motivation of other factors and centralize it to depict what and how English as a second language learned by an Indonesian who pursued his study. The interview data was qualitatively analysed to portray the situation as well as to demonstrate wider explanations of how the process was going on. The analysis shows that motivation played the most factor despite intertwined and established to the other factors of the construction of second language acquisition. Furthermore, the result of this study could seek second language learners to consider their most influencing factors in adapting themselves in learning second language.